2005
DOI: 10.1093/rheumatology/kei219
|View full text |Cite
|
Sign up to set email alerts
|

VIP down-regulates TLR4 expression and TLR4-mediated chemokine production in human rheumatoid synovial fibroblasts

Abstract: We demonstrate that VIP down-regulates LPS and TNF-alpha activation of TLR4 expression and the TLR4 functional response in terms of proinflammatory chemokine production. These studies suggest that the pleiotropic anti-inflammatory actions of VIP involve inhibitory effects on TLR4 expression and signalling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
60
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 40 publications
6
60
0
Order By: Relevance
“…Several studies in the murine model of collagen-induced arthritis have shown that VIP or PACAP potently inhibits inflammatory and autoimmune components, protecting the joints from structural damage (5,6,28). Our previous findings in human synovial cells confirm some antiinflammatory effects of VIP under both constitutive and TNF␣-or Toll-like receptor 4-stimulated conditions (12,29). A less developed concept is the potential endogenous participation of these neuropeptides in the pathogenesis of inflammation, either as endogenous mediators counterbalancing proinflammatory signaling or as permissive factors, if they are down-regulated during inflammatory responses.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Several studies in the murine model of collagen-induced arthritis have shown that VIP or PACAP potently inhibits inflammatory and autoimmune components, protecting the joints from structural damage (5,6,28). Our previous findings in human synovial cells confirm some antiinflammatory effects of VIP under both constitutive and TNF␣-or Toll-like receptor 4-stimulated conditions (12,29). A less developed concept is the potential endogenous participation of these neuropeptides in the pathogenesis of inflammation, either as endogenous mediators counterbalancing proinflammatory signaling or as permissive factors, if they are down-regulated during inflammatory responses.…”
Section: Discussionsupporting
confidence: 74%
“…Although clinical trials of VIP or related neuropeptides in human inflammatory diseases have not been performed, our previous studies demonstrated that exogenous VIP modulates different proinflammatory pathways ex vivo in human rheumatoid arthritis (RA) synovial cells (11,12). The detection of several neuropeptides, including VIP, in human arthritic joints suggests that endogenous VIP might play a regulatory role in response to joint inflammation (13,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in agreement with the higher expression of Wnt responsive genes, such as WISP1, in OA, 47 which has been associated with a profibrotic and antichondrogenic OA-like phenotype. 48 This…”
Section: Q17mentioning
confidence: 99%
“…50 Thus, in addition to integrins, Fn-fs, as an endogenous ligand of Toll-like receptors 2 and 4, could act through its engagement, given that both receptors are present in SF. 48,51 Moreover, both stimuli induce the activation of MAPK signaling, implicated in the activation of Runx2 and other transcription factors, such as the NF-kB, 13e15,46,52 which also induce the expression of Wnt. 53,54 Therefore, we can hypothesize that IL-1b and 45-kDa Fn-fs induce aggrecanases expression by activation of the transcription factor Runx2, mainly through the ERK-MAPK signaling.…”
Section: Q18mentioning
confidence: 99%